Library Research Siswa Mts Menulis Ayat Al-Qur'an Dalam Pembelajaran Al-Qur'an Hadits - Winda Winda; Santiani Santiani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the ability to write Quranic verses among students of Madrasah Tsanawiyah (MTs) in the learning of Quranic Hadith. The background of this research is the low writing skills of the Quran among students, influenced by various factors such as learning motivation, teaching methods, and social environment support. The method used is library research, collecting data using the Publish or Perish (PoP) application and analyzing data from relevant literature using the VOSviwer application. The results show that many students face difficulties in correctly writing Quranic verses, hindering the achievement of learning objectives. The implications of these findings highlight the need for more innovative and interactive teaching methods, as well as support from teachers and parents to enhance student motivation and writing skills. This research is expected to contribute positively to the development of Quranic learning in formal educational institutions.